Análise dos fatores relacionados do diagnóstico de enfermagem perfusão tissular periférica ineficaz em diabéticos - Gontijo, Paula Vitória Costa (2024)
Diabetic patients have a higher prevalence of macrovascular complications, such as peripheral vascular disease. These changes occur due to high blood glucose levels, which in the long-term result in the narrowing of small and large vessels, reducing blood flow and altering tissue perfusion. In this context, NANDA International Ineffective Peripheral Tissue Perfusion (IPTP) (NANDA-I) may be present in people with diabetes mellitus. Little research addresses the validation of the etiological factors (EF) that lead to the occurrence of this diagnosis in diabetic patients, therefore, this research aimed to analyze the EF of the nursing diagnosis Ineffective peripheral tissue perfusion in diabetic adults. This study was divided into two stages, namely: Scope review of possible causal factors for changes in peripheral tissue perfusion and validation of the etiological factors of IPTP referred to in NANDA-I and identified in the review. In the first stage, a scoping review was carried out using four databases (CINAHL, Lilacs, Scielo, Web of Science) and portal (PubMed), using the following descriptors and equivalent in English: Diabetes Mellitus, Risk factor, Perfusion, Ineffective. After applying the inclusion and exclusion criteria and quality assessment instruments, 11 articles were included in the review. 11 etiological factors were identified, Systemic arterial hypertension, Sustained hyperglycemia, Obesity, Atherosclerosis, Endothelial dysfunction, Aging, Insulin resistance, Sensory and autonomic neuropathy, Hypercholesterolemia, Smoking and/or Vitamin D deficiency. In the second stage, a study was developed with the objective of analyzing the possible causal relationships between etiological factors described in NANDA-I and identified in the literature and the occurrence of IPTP in people with diabetes mellitus. To this end, a cross-sectional study was carried out with 150 diabetic adults, followed in primary care, in Imperatriz, Maranhão. Data collection was carried out through interviews and physical examination and investigated a total of 17 clinical indicators and 13 etiological factors, among those identified in the review and those present in NANDA-I. The significance level adopted in the study was 5%. The majority of the sample was female, self-reported as mixed race, married, retired, non-smokers and alcohol drinkers. The prevalence of IPTP was 69.0%. The clinical indicators with high sensitivity were: Altered skin characteristics, Intermittent claudication, Pain in the extremity, paresthesia, Pale skin color when elevating the limb and Color does not return to the leg when it is lowered after 1 minute of its elevation. Regarding specificity, the indicators that presented the highest values were Femoral bruit, Ankle-brachial index, Edema, Delay in peripheral wound healing, Decrease in blood pressure in extremities, Intermittent claudication, Decreased peripheral pulses, Distance in the walking test. 6 minutes below normal range, Absence of peripheral pulses and Paresthesia. Of the 13 possible etiological factors of ineffective peripheral tissue perfusion, only the factors Systemic arterial hypertension and Aging showed a statistically significant association with the presence of IPTP, that is, the presence of these factors represents an increase in the chance of people with diabetes mellitus manifesting IPTP. It was concluded that the proposed thesis was confirmed, indicating the existence of new etiological factors for IPTP in diabetic people.